Treatment with estrogen receptor agonist ER beta improves torsion-induced oxidative testis injury in rats - YILDIRIM, ALPER; YEGEN, BERRAK; ERCAN, FERİHA; YÜKSEL, MERAL; ARABACI TAMER, SEVİL (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
Aims: The purpose of the present study was to investigate the potential antioxidant, anti-apoptotic and sperm function-preserving effects of estrogen, estrogen receptor (ER) a and ER beta agonists in a rat model of testis torsion-detorsion (T/D). Main methods: Under anesthesia, 6-8-week-old male Sprague-Dawley rats underwent sham-operation or testicular torsion by fixing left testis rotated at 720 degrees for 2 h. After detorsion, rats were treated with ER alpha agonist (1 mg/kg/day, subcutaneously, sc) or ER beta agonist (1 mg/kg/day, sc) or estradiol (E-2, 1 mg/kg/day, in drinking water) or vehicle on the following two days. On the third day, testicular blood-flow was recorded and then left testes were extracted for molecular and histochemical analysis. Key findings: The findings showed that reduced testicular blood-flow following torsion was partially restored on the 3rd day of detorsion, while treatments with either of the ER agonists or E-2 returned blood flow fully back to the control levels. When the testis-torsioned rats were given ER beta agonist during the detorsion period, tubular injury was lessened, sperm count and motility were increased, while the production of reactive oxygen meta-bolites and apoptosis in the testis tissues were totally suppressed. Although a down-regulated expression of androgen receptor (AR) along with a reduction in serum testosterone level was observed in the vehicle-treated T/D group, all three treatments up-regulated the expressions of AR and its mRNA, while ER alpha agonist and E-2 suppressed the testosterone level. Significance: ER beta receptor activation during the post-ischemic period may be beneficial in protection against torsion-related oxidant testicular injury and infertility.
Keywords: Testicular torsion; Estrogen; Infertility; Sperm; Apoptosis; Oxidative injury; ISCHEMIA-REPERFUSION; TESTICULAR TORSION; GENE-EXPRESSION; NITRIC-OXIDE; ALPHA; MECHANISMS; AROMATASE; PARAMETERS; APOPTOSIS; LIGANDS